2004
DOI: 10.1055/s-2004-813642
|View full text |Cite
|
Sign up to set email alerts
|

Hochauflösende Bildgebung beim Pankreaskarzinom: Prospektiver Vergleich von MRT und 4-Zeilen-Spiral-CT

Abstract: CT and MRI showed comparable results in the detection of pancreatic carcinomas as well as in the determination of resectability. Chronic pancreatitis as a "tumor-like-lesion" was the major factor of a missed diagnosis. The results of multi-reader analysis for both reading groups were almost identical with a moderate to good kappa correlation. There is no reason to prefer MRI (more expensive) over CT for patients with the presumptive diagnosis of pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In case of an uncertain diagnosis after (repeated) MDCT scan or EUS, additional imaging with ERCP with biopsy and brush should be performed to identify patients with pancreatic or periampullary malignancies [12]. The value of an additional MRI (or MRCP) in patients with obstructive jaundice without a suspected mass or other cause of obstruction requires further investigation, since the overall detection rate for pancreatic carcinoma is comparable to MDCT [20,21,22]. MDCT is superior to MRI in the assessment of locoregional extension of pancreatic carcinomas, since 3D reformations are excellent to delineate arterial or venous encasement [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…In case of an uncertain diagnosis after (repeated) MDCT scan or EUS, additional imaging with ERCP with biopsy and brush should be performed to identify patients with pancreatic or periampullary malignancies [12]. The value of an additional MRI (or MRCP) in patients with obstructive jaundice without a suspected mass or other cause of obstruction requires further investigation, since the overall detection rate for pancreatic carcinoma is comparable to MDCT [20,21,22]. MDCT is superior to MRI in the assessment of locoregional extension of pancreatic carcinomas, since 3D reformations are excellent to delineate arterial or venous encasement [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that contrast-enhanced MDCT was superior to MRI for detection of pancreatic cancer (sensitivity, 100% vs 82%Y94%), with less interobserver variability. 26 In our preliminary experience using gadolinium-enhanced MRI at 3.0 T and 64-row MDCT, the diagnostic accuracy of both methods is equivalent. Magnetic resonance imaging may be slightly superior for detection of small tumors, and 64-row MDCT has advantages in demonstration of vascular infiltration because of its superior spatial resolution.…”
Section: Detection Of Adenocarcinoma: Mri Versus Ctmentioning
confidence: 88%
“…23,33 Occasionally, MRI may detect small liver metastases not detected by CT. 18 However, with the development of MDCT with its multiplanar imaging capability, contrast-enhanced MDCT may be more efficient than gadolinium-enhanced MRI for pancreatic cancer detection and staging. 26 Pancreatic adenocarcinoma is often associated with chronic pancreatitis, not by coincidence, because chronic pancreatitis bears a dramatically increased risk to develop cancer. Both diseases show decreased signal intensity on T2-weighted GRE images and decreased contrast enhancement of masslike lesions.…”
Section: Mri Stagingmentioning
confidence: 99%
“…Contrast-enhanced techniques for both CT and MRI, combined with multiplanar reconstruction and maximal intensity projection post-processing, have improved the capability to identify and stage the extent of the tumor and extra-pancreatic involvement [ 25 ] , especially vascular arterial and venous infiltration, with an accuracy for resectability of about 90% for both CT and MRI in a direct comparison [ 26 , 27 ] .…”
Section: Staging Of Pancreatic Carcinomamentioning
confidence: 99%